Study on Hydrological Prediction of Qingshui River Basin Based on PRECIS Regional Climate Model - MA Wenjing; PAN Zhangrong; LIU Zhenlu (Renmin Zhujiang)
Frequent occurrences of extreme weather will lead to unstable changes in rivers' hydrological conditions.The SWAT hydrological model is used to simulate and verify the runoff at the Quanyanshan hydrometric station in Qingshui River,and then the runoff change at the Quanyanshan station in the Qingshui River Basin by the middle and end of the 21st century is simulated based on the PRECIS regional climate model.The results show that by the middle and end of the 21st century,with the increase in temperature and the decrease in rainfall,the runoff volume of the Qingshui River will drop.Specifically,by the middle of the 21st century,the simulated runoff volumes are basically the same under two scenarios.However,by the end of the 21st century,the simulated runoff volume is larger than that under the SSP4.5 scenario due to the higher predicted rainfall under the SSP8.5 scenario.